Method for researching diffusion stress of lithium ion battery by constructing high-fidelity microstructure model

By constructing a three-dimensional isomerial electrochemical-force coupling model, combining electrode and particle size, the problem that the existing model cannot simulate the microstructure of the real electrode is solved, and the accurate study of the diffusion stress and electrochemical properties of lithium-ion batteries is achieved, providing theoretical support for battery performance optimization and failure prevention.

CN119558132AActive Publication Date: 2025-03-04XIANGTAN UNIV

Patent Information

Application Number
CN202411653262.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-04
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

The existing models cannot accurately simulate the microstructure of the real electrode of lithium-ion batteries, and cannot effectively study the diffusion stress, electrochemical performance and electrode failure phenomena of lithium-ion batteries.

Method used

A three-dimensional heterogeneous electrochemical-force coupling model is used, combining the electrode scale and particle scale two dimensions, tomography is performed through synchronous radiation X-ray tomography microscopy to establish a high-fidelity microstructure model to study the diffusion stress, electrochemical properties and electrode failure phenomena of lithium-ion batteries.

Benefits of technology

Accurate calculation of the lithium ion concentration distribution and diffusion stress distribution in lithium ion batteries is achieved, and the impact of the opposite sex, uniformity and porosity of the electrode on battery performance can be studied, and theoretical guidance is provided for preventing battery failure and capacity attenuation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119558132A_ABST
    Figure CN119558132A_ABST
Patent Text Reader

Abstract

The invention discloses a method for researching diffusion stress of a lithium ion battery by constructing a high-fidelity microstructure model. The method comprises the following steps: firstly, performing tomography on an electrode material by using a synchrotron radiation X-ray tomography microscope, identifying active particles in the electrode material, calculating geometric parameters such as spatial distribution and volume radius of the particles, and establishing a three-dimensional geometric model of the lithium ion battery; based on mathematical models such as a reaction mechanism, a kinetic equation and a mechanical equilibrium equation of the lithium ion battery, a three-dimensional heterogeneous electrochemical-force coupling model is constructed, initial and boundary conditions are set for the model, grids are divided, and finite element calculation is carried out. According to the invention, the distribution of diffusion stress and the relationship between the distribution of diffusion stress and lithium ion concentration can be analyzed, and meanwhile, the electrode characteristics such as porosity, curvature, anisotropy and uniformity of the electrode can be analyzed. And battery failure phenomena such as particle breakage and particle stripping can be avoided, and theoretical guidance can be provided for preventing battery failure and capacity fading.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion battery simulation modeling, and specifically relates to a method for constructing a high-fidelity microstructure model to study the diffusion stress of lithium ion batteries. Background Art

[0002] In the past few decades, with the rapid development of science and technology and the increase in population, people have become more and more dependent on energy. Traditional energy sources such as coal, oil, and natural gas have been over-exploited and used, leading to increasingly serious energy crises and environmental pollution problems. Therefore, many countries are working hard to find more environmentally friendly energy sources to promote low-carbon production and further alleviate the problem of global warming. In order to reduce dependence on fossil fuels, the country actively encourages the use of new energy to replace fossil fuels and vigorously supports the development of new energy vehicles. Lithium-ion batteries have become the ideal power battery for new energy vehicles with their high energy density, high operating voltage, low self-discharge rate, and environmental friendliness. It is also a very promising energy storage device.

[0003] During the insertion and extraction of lithium ions, the electrode particles will expand and shrink, resulting in a volume change of the electrode material. The volume change of the electrode will generate stress at the particle scale, namely diffusion stress. Excessive diffusion stress will cause cracking and fracture of particles, separation between particles, cracking and fracture of the active layer, etc., resulting in battery capacity decay, increased internal resistance, decreased rate performance and decreased cycle life. Traditional experimental methods can only obtain the apparent characteristics of the battery such as voltage, temperature, and capacity, but it is difficult to obtain the characteristics of lithium ion concentration, stress and displacement distribution inside the battery. It is becoming increasingly clear that the development of the next generation of higher performance lithium-ion batteries will require joint efforts between experimentalists and simulators. Therefore, in addition to more advanced experimental characterization methods, better and more advanced verification tools and prediction models are also very important. Numerical simulation methods are widely used in lithium-ion battery research due to their advantages such as short calculation time and low research cost. By establishing an effective model, the electrochemical and stress characteristics inside the battery can be easily obtained.

[0004] To date, there is still a disconnect between experiments and simulations in the study of the microstructure on porous electrodes. Although some progress has been made in the simulation and calculation of electrode microstructures in the past few decades, there are still some differences between the simulated microstructure and the real battery microstructure. At present, the research on diffusion stress of lithium-ion batteries is mainly focused on the single particle scale, and is mainly based on one-dimensional electrochemical-force models. This type of model can only analyze the stress size of a single electrode particle, and cannot obtain the stress distribution between particles, and cannot simulate the lithium concentration distribution and stress distribution inside the battery. There are also some simplified three-dimensional models that study the electrochemical and stress characteristics inside the electrode by constructing some equal-volume spheres instead of electrode particles, but they all differ from the real structure. Summary of the invention

[0005] In view of the technical problem that the existing models cannot simulate the real electrode microstructure, the present invention provides a method for constructing a high-fidelity microstructure model to study the diffusion stress of lithium-ion batteries. The method constructs a three-dimensional heterogeneous electrochemical-mechanical coupling model based on the real microstructure of the electrode to study the diffusion stress, electrochemical performance and electrode failure phenomenon of lithium-ion batteries. The model combines the two dimensions of electrode scale and particle scale, and can obtain the macroscopic performance of the battery and the characteristics of the diffusion stress concentration distribution inside the battery. At the same time, for the same chemical system, the electrochemical performance and stress distribution of different mass proportions and different compaction densities of positive electrode active materials are studied, and the influence of active material proportion and compaction density on battery performance and particle diffusion stress is analyzed, providing theoretical guidance for preventing battery failure and slowing down capacity decay.

[0006] The technical solution adopted by the present invention is as follows:

[0007] The method of constructing a high-fidelity microstructure model to study the diffusion stress of lithium-ion batteries includes the following steps:

[0008] S1. Use synchrotron radiation X-ray tomography to scan the electrode material, identify the active particles in the electrode material, calculate the geometric parameters of the particles, establish the geometric model of the lithium-ion battery, set the boundary conditions and perform meshing;

[0009] S2. Based on the electrochemical reaction mechanism and mechanical equilibrium equation inside the lithium-ion battery, a three-dimensional heterogeneous electrochemical-mechanical coupling model is established by combining the three-dimensional geometric model obtained in S1 and the electrochemical parameters and mechanical parameters of the battery materials;

[0010] S3. Calculate the lithium ion concentration distribution, charge and discharge curves, electrochemical characteristics and diffusion stress distribution of lithium ion batteries during the charge and discharge process according to the three-dimensional heterogeneous electrochemical-mechanical coupling model obtained in S2. Based on these basic characteristics, further study the effects of the anisotropy, uniformity and porosity of the electrodes on the battery performance and failure phenomena including particle fracture and peeling.

[0011] S4. Based on the three-dimensional heterogeneous electrochemical-mechanical coupling model and the calculated data, a three-dimensional model with different active material proportions and different compression forces is constructed while keeping the material parameters unchanged. The differences in diffusion stress and electrochemical performance are compared and analyzed to optimize the battery structure and process.

[0012] Furthermore, in S1, the establishment of a three-dimensional geometric model includes particle-scale modeling and electrode-scale modeling. The particle-scale modeling is specifically as follows: experimentally characterize the electrode material, use a scanning electron microscope to obtain the morphological characteristics of the electrode, then perform tomography on the electrode to obtain the layered microstructure of the electrode, use an algorithm to calculate the particle size distribution of the electrode particles, calibrate the spatial coordinates of the particles, calculate the radius of the particles, and then use programming to import these geometric parameters into the finite element calculation software to generate a particle distribution similar to that of the actual electrode material particles. The particles are simplified to spheres, and the radius of the particles conforms to the actual electrode particles; the electrode-scale modeling is specifically as follows: obtain the geometric and mechanical parameters of the test battery separator and current collector, and then add the separator and current collector to the model to obtain the three-dimensional size of the entire lithium-ion battery. In the geometric modeling, a rectangular element is constructed to subtract the particle geometry, and the subtraction area is defined as the conductive agent and binder of the electrode. These areas are assembled into a union to obtain a three-dimensional geometric model of the lithium-ion battery.

[0013] Furthermore, in S1, the specific process of setting boundary conditions and performing meshing includes: giving electrochemical and mechanical boundary conditions to each structure in the three-dimensional geometric model, and finally performing meshing.

[0014] Furthermore, the boundary conditions specifically include:

[0015] In terms of solid-phase mass transfer, it is assumed that the lithium ion concentration in the center of the active particles is always equal to the initial concentration and does not change with time; on the particle surface, the diffusion flux is determined by Fick's first law;

[0016] In terms of liquid phase mass transfer, no-flux boundary conditions are set at the positive and negative electrode current collectors;

[0017] In terms of charge transfer, zero potential is set on the surface of the lithium negative electrode, insulating boundary conditions are set on both sides of the separator, and current density is applied to the positive electrode current collector;

[0018] In terms of mechanics, a prescribed displacement boundary condition is set on the negative electrode.

[0019] Furthermore, the meshing process specifically includes:

[0020] Use free tetrahedral meshing for the geometry.

[0021] Furthermore, in S2, the electrochemical parameters and mechanical parameters of the battery material specifically include:

[0022] The battery material system is a half-cell system with a positive electrode of ternary nickel-cobalt-manganese material and a negative electrode of lithium metal. The electrochemical parameters include the conductivity of the material, the maximum lithium concentration and initial lithium concentration of the positive electrode, the transfer number, migration number, Faraday constant and universal gas constant of the electrolyte material.

[0023] Mechanical parameters include Young's modulus, Poisson's ratio, partial molar volume and density of the material.

[0024] Furthermore, in S2, the reaction mechanism and mechanical equilibrium equations inside the lithium-ion battery include the mass conservation equation, the charge conservation equation, the electrochemical reaction kinetics equation and the constitutive equation.

[0025] Furthermore, the modeling process of S2 is as follows: after obtaining the three-dimensional geometric model, the electrochemical parameters and mechanical parameters of the battery material are input into the corresponding area of ​​the model, and then the mass conservation equation, charge conservation equation, electrochemical reaction kinetics equation and mechanical equilibrium equation are written into the model to obtain a three-dimensional electrochemical-mechanical coupling model.

[0026] Furthermore, in S3, the calculation process specifically includes: to simplify the study, a part of the electrode is selected as the representative volume element, and the lithium ion concentration distribution, electrolyte concentration distribution, and lithium ion flux in the battery particles are calculated by combining the solid-phase mass transfer, liquid-phase mass transfer, and charge transfer boundary conditions; the three-dimensional diffusion stress and strain of the battery particles are calculated by combining the lithium ion concentration distribution, the lithiation expansion coefficient of each active material, and the mechanical boundary conditions, as well as the failure phenomena including fracture and peeling analysis.

[0027] Furthermore, in S4, positive electrode materials with electrode active material mass proportions of 90wt%, 92wt%, 94wt% and 96wt% respectively and positive electrode materials with compressions of 90wt% 0bar, 90wt% 600bar, 90wt% 2000bar, 96wt% 0bar, 96wt% 600bar and 96wt% 2000bar respectively were modeled, and the electrochemical performance and diffusion stress distribution of batteries under different structures were compared to study how to optimize the electrode structure and manufacturing process.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The model proposed in the present invention combines the characteristics of both particle scale and electrode scale, and combines experimental characterization methods to establish a three-dimensional electrochemical-mechanical coupling model similar to the microstructure of real electrode particles. Through this model, the lithium ion concentration distribution and diffusion stress distribution inside the battery can be calculated, and the influence of the anisotropy, uniformity, and porosity of the electrode on the battery performance, as well as failure phenomena such as particle fracture and peeling, can be studied, which can provide theoretical guidance for preventing battery failure and capacity decay. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a schematic diagram of the overall process of the present invention.

[0031] Figure 2 It is the electrochemical-mechanical coupling principle in the present invention.s is the solid phase lithium concentration, i loc is the local charge density on the particle surface, J s is the lithium ion diffusion flux, f v is the material volume change function, σ s is the hydrostatic stress and η is the overpotential.

[0032] Figure 3 It is the electrode morphology and the spatial distribution of particles in the present invention.

[0033] Figure 4 It is a schematic diagram of the geometry and mesh division of the three-dimensional electrochemical-mechanical model of the lithium-ion battery in the present invention.

[0034] Figure 5 This is a distribution diagram of the lithium ion concentration of the positive electrode during the discharge process of the lithium ion battery in Example 1 as a function of the state of charge (SOC).

[0035] Figure 6 This is the von Mises stress distribution diagram of the positive electrode during the discharge process of the lithium-ion battery in Example 1.

[0036] Figure 7 This is the geometric model of positive electrode particles with different active material contents in Example 1.

[0037] Figure 8 von Mises stress distribution diagram of the positive electrode discharge process with different active material contents in Example 1.

[0038] Fig. 9 This is the geometric model of positive electrode particles with different compaction densities of active materials in Example 1.

[0039] Fig.10 von Mises stress distribution diagram of the positive electrode discharge process with different active material compaction densities in Example 1. DETAILED DESCRIPTION

[0040] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, but the present invention is not limited thereto.

[0041] Example 1

[0042] The overall process diagram of the present invention is as follows Figure 1 As shown, the following embodiments will establish a model and perform calculations according to this process.

[0043] The electrochemical-mechanical coupling principle of the present invention is as follows Figure 2 As shown,

[0044] In this embodiment, a ternary (NMC111) half-cell is taken as the research object. The positive electrode is the active particles of the ternary material, the negative electrode is lithium metal, and the electrolyte is lithium hexafluorophosphate (LiPF6), which is dissolved in a mixed non-aqueous organic solvent with a volume ratio of 1:2 of ethylene carbonate (EC) and dimethyl carbonate (DMC).

[0045] The modeling method specifically includes the following steps:

[0046] (1) Using the obtained particle radius parameters, combined with the particle scale and electrode scale, a three-dimensional geometric model of the lithium-ion battery is established, boundary conditions are given, and meshing is performed.

[0047] Under the scanning electron microscope, the particle morphology of the positive electrode is as follows Figure 3 (a), and then a tomographic scan is performed to calculate the spatial distribution and geometric parameters of the particles; the particles are imported into the finite element software using a programming language to obtain a preliminary three-dimensional geometric model as shown in Figure 3 (b). Taking into account the characteristics of particle size and electrode size, the particle size distribution of real electrode particles is simulated, and carbon black conductive agent and binder are added to form a half-cell with metallic lithium. The positive electrode and the separator are both immersed in the electrolyte. To simplify the calculation, the representative volume element is selected as Figure 4 (b).

[0048] When setting boundary conditions, in terms of solid phase mass transfer, it is assumed that the lithium ions in the center of the active particles are always equal to the initial concentration and do not change with time. On the particle surface, the diffusion flux is determined by Fick's first law; in terms of liquid phase mass transfer, a no-flux boundary condition is set at the positive electrode current collector; in terms of charge transfer, a zero potential is set on the lithium metal surface, an insulating boundary condition is set on both sides of the diaphragm, and a current density is applied to the positive electrode current collector; in terms of mechanics, a specified displacement boundary condition is set on the current collector.

[0049] Mesh division is performed. First, the positive electrode active particle domain is meshed using free tetrahedral meshing, and then the remaining area of ​​the model is meshed using free tetrahedral meshing. Finally, the model consists of 83122 triangle units, 594565 tetrahedral units, 9970 edge units, and 3503 vertex units. The final mesh division diagram is shown in the figure below. Figure 4 (c) as shown.

[0050] (2) Based on the internal reaction mechanism and mechanical equilibrium relationship of lithium-ion batteries, a three-dimensional electrochemical-mechanical model is established according to the three-dimensional geometric model of lithium-ion batteries and the electrochemical parameters and mechanical parameters of battery materials.

[0051] The electrochemical parameters of battery materials include the conductivity of the material, the maximum lithium concentration and initial lithium concentration of the positive electrode, the transfer number, the migration number, the Faraday constant and the universal gas constant, as shown in Table 1.

[0052] Table 1 Electrochemical parameters of battery materials

[0053]

[0054]

[0055] The mechanical parameters of battery materials include Young's modulus, Poisson's ratio and density, as shown in Table 2.

[0056] Table 2 Mechanical parameters of battery materials

[0057]

[0058] The equations in the established three-dimensional electrochemical-mechanical model include: mass conservation equation, charge conservation equation, electrochemical reaction kinetics equation and mechanical equilibrium equation.

[0059] The mass conservation equation:

[0060]

[0061]

[0062]

[0063]

[0064] In the formula, i=n and i=p represent the negative electrode and the positive electrode respectively; c s,i is the lithium ion concentration in the solid phase; t is the discharge time; D s,i is the solid phase lithium ion diffusion coefficient; r is the radial coordinate inside the active particle; j loc is the local current density; rp i is the radius of the electrode active particle; F is the Faraday constant; D l and are the diffusion coefficient and effective diffusion coefficient of the electrolyte respectively; c l is the lithium ion concentration in the electrolyte; γ is the Bruggeman correction factor; ε l and ε s represent the volume fractions of liquid and solid phases in the porous electrode respectively; S a is the specific surface area of ​​the electrode active particles; t + is the transfer number of lithium ions.

[0065] Charge conservation equation:

[0066] ▽·i s +▽·i l =0

[0067] ▽·i s =S aj loc ▽·i l =-S a j loc

[0068]

[0069]

[0070] In the formula, i s and i l denote the current density in the solid and liquid electrolytes, respectively; is the effective conductivity of the solid phase; φ s is the electrode potential; is the effective ionic conductivity of the liquid electrolyte; φ l is the electrolyte potential; R is the universal gas constant; T is the electrolyte temperature; and f is the average molar activity coefficient.

[0071] According to the electrochemical-mechanical coupling principle, the diffusion stress of particles will affect the diffusion of lithium ions in the particles and the surface charge transfer reaction, which is specifically manifested in the diffusion equation and the kinetic equation.

[0072] Fick's Law - Lithium Diffusion Equation:

[0073] J=-Mc s ▽μ

[0074] μ=μ0-Ωσ h

[0075]

[0076] The diffusion flux of the electrode particles J s The diffusion of lithium ions is regulated by diffusion stress.

[0077] Electrochemical reaction kinetics equation:

[0078]

[0079]

[0080]

[0081] Where η is the overpotential, which is regulated by the diffusion stress on the charge transfer reaction on the particle surface, j0 is the current density on the electrode surface; α a and α c represent the oxidation reaction transfer coefficient and the reduction reaction transfer coefficient respectively; E eq,i represents the equilibrium potential; k0 is the reaction rate constant; c s,max and c s,surfare the maximum lithium ion concentration in the active material particles and the lithium ion concentration on the surface of the active particles, respectively.

[0082] Mechanical equilibrium equation:

[0083]

[0084]

[0085]

[0086]

[0087]

[0088]

[0089]

[0090]

[0091]

[0092] Where ΔV is the volume change of the particle; V0 is the initial volume; f v is the particle volume change function; ε ij is the strain component; σ ij is the stress component; E is Young's modulus; v is Poisson's ratio; ε r and ε θ represent radial strain and tangential strain respectively; σ r and σ θ Represent radial stress and tangential stress respectively; σ h and σ M represent the hydrostatic stress and vonMises stress respectively.

[0093] (3) The lithium ion concentration and diffusion stress distribution of lithium ion batteries during the charge and discharge process are calculated based on a high-fidelity three-dimensional electrochemical-mechanical model of the lithium ion battery microstructure.

[0094] According to the three-dimensional electrochemical-mechanical model, combined with the solid-phase mass transfer, liquid-phase mass transfer and charge transfer boundary conditions, the discharge simulation calculation was carried out under the conditions of ambient temperature of 20°C and discharge rate of 5C. The maximum charging voltage was 4.3V, the discharge cut-off voltage was 3.0V, and the lithium ion concentration distribution of the electrode particles at different discharge depths of the battery during the discharge process was as follows: Figure 5 Combined with the lithium expansion coefficient and mechanical boundary conditions of each active material, the three-dimensional von Mises stress distribution of the positive electrode particles is calculated as follows: Figure 6 shown.

[0095] (4) According to the construction method of the model, the mass proportion and compaction density of the active material in the electrode are changed while other parameters remain unchanged, and the diffusion stress distribution of the electrode is compared and analyzed.

[0096] To ensure that the chemical system remains unchanged, a three-dimensional model was constructed for different active material mass proportions, where particle models with different contents are as follows: Figure 7 As shown in the figure, the mass proportions of active materials are 90wt%, 92wt%, 94wt% and 96wt% respectively. Then the diffusion stress distribution of electrodes with different active material contents is compared. The von Mises stress distribution of positive electrodes with different contents is shown in the figure. Figure 8 Similarly, when the mass proportion is 90wt% and 96wt%, particle models with different compaction densities are constructed as shown in Fig. 9 As shown in the figure, the pressures applied in the rolling process are 0 MPa, 70 MPa and 240 MPa respectively. The positive electrode vonMises stress distribution corresponding to the model is shown in Fig.10 By comparing the stress and electrochemical performance corresponding to these parameters, the electrode manufacturing process can be optimized to alleviate battery failure and extend battery life.

[0097] In summary, it can be seen that the method of the present invention can obtain the three-dimensional lithium concentration distribution and three-dimensional diffusion stress distribution of electrode particles. At the same time, it can optimize battery performance and reduce diffusion stress by changing the electrode manufacturing process, which can provide theoretical guidance for preventing battery failure and capacity attenuation.

Claims

1. A method for constructing a high-fidelity microstructure model to study the diffusion stress of lithium-ion batteries, characterized in that: The steps include: S1. Use synchrotron radiation X-ray tomography to scan the electrode material, identify the active particles in the electrode material, calculate the geometric parameters of the particles, establish a three-dimensional geometric model of the lithium-ion battery, set boundary conditions and perform meshing; S2. Based on the reaction mechanism and mechanical equilibrium equation inside the lithium-ion battery, a three-dimensional heterogeneous electrochemical-mechanical coupling model is established in combination with the three-dimensional geometric model of the lithium-ion battery obtained in S1 and the electrochemical parameters and mechanical parameters of the battery materials; S3. Calculate the lithium ion concentration distribution, charge and discharge curves, electrochemical characteristics and diffusion stress distribution of lithium ion batteries during the charge and discharge process according to the three-dimensional heterogeneous electrochemical-mechanical coupling model obtained in S2. Based on these basic characteristics, further study the effects of the anisotropy, uniformity and porosity of the electrodes on battery performance, as well as failure phenomena including particle fracture and peeling. S4. Based on the three-dimensional heterogeneous electrochemical-mechanical coupling model and the calculated data, a three-dimensional model with different active material proportions and different compaction densities is constructed while keeping the material parameters unchanged. The differences in diffusion stress and electrochemical performance are compared and analyzed to optimize the battery structure and process.

2. The method for constructing a high-fidelity microstructure model to study the diffusion stress of lithium-ion batteries according to claim 1, characterized in that: In S1, the three-dimensional geometric model is established, including particle-scale modeling and electrode-scale modeling; The particle size modeling is specifically as follows: The electrode material is experimentally characterized, and the morphological features of the electrode are obtained using a scanning electron microscope. The electrode is then tomographically scanned to obtain the layered microstructure of the electrode, and the particle size distribution of the electrode particles is calculated. The spatial coordinates of the particles are calibrated, and the radius of the particles is calculated. These geometric parameters are then imported into the finite element calculation software using a programming language to generate a particle distribution similar to that of the real electrode material particles. The particles are simplified into spheres, and the radius of the particles conforms to that of the real electrode particles. The electrode scale modeling is specifically as follows: the geometric parameters of the separator and the current collector of the test battery are obtained, and then the separator and the current collector are added to the model to obtain the three-dimensional size of the entire lithium-ion battery. In the geometric modeling, rectangular elements are constructed and subtracted from the particle geometry, and the subtracted areas are defined as the conductive agent and the binder of the electrode. These areas are assembled into a union to obtain the three-dimensional geometric model of the lithium-ion battery.

3. The method for constructing a high-fidelity microstructure model to study the diffusion stress of lithium-ion batteries according to claim 1, characterized in that: In S1, the boundary conditions and the specific process of meshing include: Electrochemical and mechanical boundary conditions are given to each structure in the three-dimensional geometric model, and finally meshing is performed.

4. The method for constructing a high-fidelity microstructure model to study the diffusion stress of lithium-ion batteries according to claim 1 or 3, characterized in that: The boundary conditions specifically include: In terms of solid-phase mass transfer, it is assumed that the lithium ions in the center of the active particles are always equal to the initial concentration and do not change with time; At the particle surface, the diffusion flux is determined by Fick’s first law; In terms of liquid phase mass transfer, no-flux boundary conditions were set at the positive and negative electrode current collectors; In terms of charge transfer, zero potential is set on the surface of the lithium metal negative electrode, insulating boundary conditions are set on both sides of the separator, and current is applied to the positive electrode current collector; In terms of mechanics, a prescribed displacement boundary condition is set on the positive electrode current collector.

5. The method for constructing a high-fidelity microstructure model to study the diffusion stress of lithium-ion batteries according to claim 1 or 3, characterized in that: The meshing process specifically includes: The active particles in the cathode domain are meshed using free tetrahedral meshing first, and then the rest of the model is meshed using free tetrahedral meshing.

6. The method for constructing a high-fidelity microstructure model to study the diffusion stress of lithium-ion batteries according to claim 1, characterized in that: In S2, the electrochemical and mechanical parameters of battery materials specifically include: Electrochemical parameters include the conductivity of the material, the maximum and initial lithium concentrations of the cathode, the transfer number, the migration number, the Faraday constant, and the universal gas constant; Mechanical parameters include Young's modulus, Poisson's ratio and density of the material.

7. The method for constructing a high-fidelity microstructure model to study the diffusion stress of lithium-ion batteries according to claim 1, characterized in that: In S2, the control equations such as the reaction mechanism and mechanical equilibrium relationship inside the lithium-ion battery include the mass conservation equation, charge conservation equation, electrochemical reaction kinetics equation and mechanical equilibrium equation.

8. The method for constructing a high-fidelity microstructure model to study the diffusion stress of lithium-ion batteries according to claim 1, characterized in that: In S3, the calculation process specifically includes: By combining solid-phase mass transfer, liquid-phase mass transfer and charge transfer boundary conditions, the lithium ion concentration distribution within the battery particles is calculated; by combining the lithium ion concentration distribution, the lithiation expansion coefficient of each active material and the mechanical boundary conditions, the three-dimensional diffusion stress distribution of the battery particles is calculated.

9. The method for constructing a high-fidelity microstructure model to study the diffusion stress of lithium-ion batteries according to claim 1, characterized in that: In S4, under the condition of keeping the material parameters unchanged, three-dimensional models with different active material proportions and different compaction densities were constructed to compare and analyze the differences in diffusion stress and electrochemical performance. Specifically, the following are included: The positive electrode materials with electrode active material mass proportions of 90wt%, 92wt%, 94wt% and 96wt% and the positive electrode materials with electrode rolling pressures of 90wt% 0bar, 90wt% 600bar, 90wt% 2000bar, 96wt% 0bar, 96wt% 600bar and 96wt% 2000bar were modeled respectively, and the electrochemical performances and diffusion stress distribution of the batteries under different structures were compared to study how to optimize the electrode structure and manufacturing process.

Citation Information

Patent Citations

  • Lithium ion battery multi-physical field electrochemical-force-phase field coupling model and modeling method

    CN117725798A

  • Method for researching diffusion stress of lithium ion battery based on three-dimensional electrochemical-force model

    CN118296842A

Cited By

  • Lithium ion battery polycrystal / single crystal positive electrode material multi-physics field coupling modeling and failure analysis method

    CN120388664A

  • High-throughput modeling and calculating method and system for metal-based composite material

    CN120995785A

  • A high-throughput modeling and computing method and system for metal matrix composites

    CN120995785B

  • Battery detection method and system based on CT imaging and multi-physical field simulation

    CN121740917A